SOCIO-DEMOGRAPHIC CORRELATES OF CAREGIVER BURDEN IN SCHIZOPHRENIA: A STUDY AT NEUROPSYCHIATRIC HOSPITAL ARO, NIGERIA - Ighedosa, Osemhen Bartholomew; Eriamiantoe, Osaigbovo Festus; Ighedosa, Evelyn Benahi; Ukponahiusi, Owie (African Journal of Social and Behavioural Sciences, 2025)
This study assessed the level of care burden and its correlates among caregivers of patients with a diagnosis of schizophrenia in Neuropsychiatric Hospital Aro, Abeokuta, Ogun State, South-West Nigeria. The cross-sectional research survey design was used with a sample size of 244, which were randomly selected from the total population of caregivers and spanned over a period of four months. The socio-demographic questionnaire and Zarit Burden Interview (ZBI) were administered for data collection, while the Psychotic Module of MINI-Plus was used to revalidate the diagnosis of schizophrenia. The association between caregivers' socio-demographic variables and care burden was tested using chi-square while regression analysis was done to identify independent predictor(s) of care burden. Findings revealed that 17.2% of participants experienced a high burden, and those who spent 36 hours or more per week in the caregiving role had a significantly higher proportion (40.6%) of a high burden compared with those who spent less than 36 hours (8.9%) (χ2 = 33.369; df = 1; p < 0.001). It was discovered from the findings that primary caregivers of patients with schizophrenia experience a high degree of burden. For example, a greater proportion of high caregiver burden was found among caregivers whose duration of relationship with the patient was more than 30 years (26.0%) compared with those whose duration of relationship was 30 years or less (11.1%) (χ2 = 9.181; df = 1; p = 0.002). This study, therefore, serves as a reminder that aside from caring for our patients, there is an increasing need to improve the social support available to caregivers who are the "unseen patients" and whose well-being is inseparably intertwined with that of the patients.